ISLAMIC VIEW OF HUMAN RIGHTS - Dini Nur Islamiyati (UNISSULA, 2017)
Human Right is an important issue to be discussed, moreover in the West countries. This is because Human Right is talking about human being. Eventhough this concept was born and developed in the West, but East countries, which Islam becomes the majority, adapt this concept slowly to be included in the state law. Islamic concept is believed as the way of life by its adherents. Islam according to its adherents is a complete concept that rule every aspects in the human’s life, no exception in the regulation of Human Right. Islam as a religion means rahmatan lil ‘alamin, which means mercy for the universe, even in the social injustice Islam regulates about the concept of Human Right. This article purposes to know about the history of Human Right and how Islam views the concept of it.